Analysis of explication aspect by Malay students in the teaching of English vocabulary - Subramaniam, Vijayaletchumy; Wan Mohammad, Wan Muna Ruzanna; Yong, Chyn Chye; Elangkovan, Nertiyan (Canadian Center of Science and Education, 2011)
This paper is focusing on how far is the explication aspect can help in enhancing the Malay students’ progress in English vocabulary. Children in school have a variety of language mastering levels and they are different from one and another. Their results in the examination has proven that the particular situation to be true. Therefore, such awareness urges researcher on doing a research to identify the mastering levels among the subjects in the research. The research was conducted based on two target groups; excellent and average group. There were 20 students involved from these two groups. Based on the data obtained from the Form Five students, it was found that the explication aspect could actually help in enhancing the Malay students’ progress in English vocabulary. This research was done in two schools and they were Sekolah Kebangsaan Serdang and Sekolah Kebangsaan Dengkil, Selangor.